PENGGUNAAN VERBA FRASAL OLEH SISWA SMA NEGERI 2 MANADO - MATHEOSZ, STACEY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The title of this study is â€œThe Use of Phrasal Verbs by the Students of SMA Negeri 2 Manadoâ€. The main object of this study is the use of phrasal verbs by the XI grade students of SMA Negeri 2 Manado (Mathematics and Natural Sciences class). The method that has been applied by the writer in this research is descriptive method which has been done in several stages: preparation was made by reading the theory about phrasal verbs and goingto the school to get a picture of the English curriculum. Data collection was taken from 40 students of SMA Negeri 2 Manado, by giving them tests containing phrasal verbs. They are multiple choice, fill in the blank and true or false. The indentified data were analyzed by using simple statistic and qualitative method based on Furchon (1982). The result of the test is described by using some tables. The result of the analysis shows that the studentâ€™s difficulty in using phrasal verbs is high; that is only 36.8% of the students have right answer while 63.2% have wrong answer. The difficulty is caused by the misunderstanding of the meaning of phrasal verbs. Some of the students do not understand what the phrasal verbs are and how to use phrasal verbs in a sentences due to the minimum teaching of phrasal verbs in SMA Negeri 2 Manado. Â Key words : phrasal verb, students, misunderstanding, use, presentage